Model Aplikasi Pengolahan Data Keuangan Pada Sekolah Dasar - Dwi Mulyani; Masniah Masniah; Riyan Riyan (STMIK Banjarbaru, 2022)
The Integrated Islamic Elementary School (SDIT) Babul Jannah Banjarbaru is a private school in the city of Banjarbaru that uses Islamic education methods. In the financial administration process at SDIT Babul Jannah Banjarbaru it is done manually by recording finances in an ordinary journal. At the time of reporting at the end of the month the manager must re-type data from the journal to the computer to make financial reports. The financial management process occurs twice, so it is less effective and efficient. In this study, a computerized financial management application was created as a solution to solving the problems faced by SDIT Babul Jannah Banjarbaru. The results of the user acceptance test with a total of 5 questions indicate that 80% of respondents agree that this application is able to simplify and speed up financial management and speed up service to student parents. Subsequent tests produced valid data and Crounbach's alpha value was 0.94. Crounbach's alpha value of 0.94 lies between 0.80 and 1.00 so that the level of reliability is reliableKeywords: Application; Financial Management; Babbul Jannah AbstrakSekolah Dasar Islam Terpadu (SDIT) Babul Jannah Banjarbaru adalah sekolah swasta dikota Banjarbaru yang menggunakan metode pendidikan Islam. Dalam proses administrasi keuangan SDIT Babul Jannah Banjarbaru dilakukan secara manual dengan pencatatan keuangan pada buku jurnal biasa. Pada saat pelaporan akhir bulan pengelola harus mengetikkan kembali data dari buku jurnal ke komputer untuk membuat pelaporan keuangan. Proses pengelolaan keuangan terjadi dua kali kerja sehingga kurang efektif dan efisien. Didalam penelitian ini dibuat aplikasi pengelolaan keuangan yang terkomputerisasi sebagai solusi untuk memecahkan permasalahan yang di hadapi oleh SDIT Babul Jannah Banjarbaru. Hasil pengujian user acceptance dengan jumlah pertanyaan 5 buah menunjukkan bahwa 80% responden setuju aplikasi ini mampu mempermudah dan mempercepat pengelolaan keuangan dan mempercepat pelayanan kepada wali murid. Pengujian selanjutnya menghasilkan data yang valid dan nilai alpha crounbach adalah 0.94. Nilai alpha crounbach 0.94 terletak antara 0.80 dengan 1.00 sehingga tingkat Reliabilitasnya reliable